Avaliação dos efeitos do treinamento físico aeróbico nos parâmetros cardíacos e na capacidade funcional em modelo experimental de cardiomiopatia chagásica crônica - Thayrine Rosa Damasceno (2023)
Chronic Chagas cardiomyopathy (CCC) is the most severe form of non-ischemic cardiomyopathy in Latin America. The persistent and low-intensity infection by Trypanosoma cruzi triggers a complex and long-lasting pathogenesis leading to the development of parasite-dependent myocardial damage, immune-mediated myocardial injury, microvascular disorders and cardiac dysautonomia, which contribute to the progression of ventricular dysfunction and reduction in cardiorespiratory fitness (CRF). Few studies suggest that aerobic physical training (APT) can lead to improvement in CRF and myocardial damage. The objectives of this study were to evaluate the effects of APT on myocardial morphology, function and perfusion and correlate these variables with inflammation and fibrosis in an experimental model of CCC using high-resolution in vivo images. Additionally, to investigate the influence of these alterations in the reduction of CRF. Furthermore, as a secondary objective, to analyze the cross-sectional areas of the skeletal muscle. In order to verify the clinical application of the study, we also performed a retrospective analysis of patients with CCC. Female Syrian hamsters with CCC and their controls (CT) were allocated into four groups: CCC-APT (n=22), CCC-SED (n=22), CT-APT (n=8) and CT-SED (n= 8). Seven months after infection, the animals were submitted to two-dimensional echocardiography, myocardial perfusion scintigraphy and cardiopulmonary exercise testing. The training was carried out for eight weeks, five times a week, for fifty minutes. After completing the APT protocol, the animals were reassessed, euthanized and cardiac tissue samples were collected for histopathological analysis. In the retrospective clinical analysis, four patients with CCC performed aerobic exercise at moderate to high intensity (60 to 85% of VO2peak) for twelve weeks. In the baseline evaluation, before allocation to the groups, chagasic animals showed similar peak oxygen consumption (VO2peak) (p>0.05), increased areas of myocardial perfusion defect (MPD) [4.5(2.7-8.5) vs 2.6(0.8-3.9), p=0.014] and reduction in left ventricular ejection fraction (LVEF) [46.9(40.3 -49 .7) vs 51.7 (49.4-53.3), p < 0.001] when compared to control animals. The correlation analysis showed that VO2peak correlated with MPD (r=-660; p<0.0001), LVEF (r=0.374; p=0.022), LVDD (r=-0.533; p=0.001) and LVSD (r=-0.49; p=0.001). Only MPD remained independently associated with VO2peak (adjusted r²=0.42). After animals allocation, mixed ANOVA showed reduced LVEF in chagasic groups [CCC-SED 46.72 (40.01-51.06)%] and CCC-APT [46.87 (42.35-50.10)%; p=0.015] when compared with CT-SED [53.06 (51.95-54.00)%, pANOVA=0.009]. After APT, mixed ANOVA identified reduced LVEF, significant increase in MPD over time, and more inflammation [(1.60±0.63); pANOVA<0.0001] and type 1 collagen [1.84 (1.22-2.82); pANOVA=0.008] in the CCC-SED group, when compared to the other groups. On the other hand, APT in the CCC-APT group reduced inflammation [(0.93±0.20); pANOVA<0.0001], prevented the progression of MPD and myocardial fibrosis, attenuated left ventricular dysfunction and improved the CRF. In animals with CCC, APT reduced inflammation, prevented the progression of MPD and fibrosis, attenuated left ventricular remodeling, improved functional capacity and promoted musculoskeletal structural recovery, reducing muscle atrophy. Furthermore, in patients with CCC, APT decreased MPD, improved LVEF and CRF.